2021
DOI: 10.1002/pon.5830
|View full text |Cite
|
Sign up to set email alerts
|

Associations between markers of social functioning and depression and quality of life in survivors of head and neck cancer: Findings from the Head and Neck Cancer 5000 study

Abstract: Objective: To investigate associations between markers of social functioning (trouble with social eating and social contact), depression and health-related quality of life (QOL) among head and neck cancer survivors.Methods: This cross-sectional analysis included individuals with oral cavity, oropharynx, larynx, salivary gland and thyroid cancers from Head and Neck 5000 alive at 12 months. Trouble with social eating and social contact were measured using items from EORTC QLQ-H&N35 and QOL using EORTC QLQ-C30; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…Dysphagia is a major quality of life issue for patients treated for head and neck cancer treated either surgically or nonsurgically [19,20]. This potential longterm radiation damage has a profound impact on social functioning and mental health [21]. In order to reduce or limit these sequelae while maintaining excellent oncological outcomes, multiple paradigms have been explored with regard to treatment deescalation including cetuximab-RT [22,23], reduced-dose RT/CRT [24][25][26], induction chemotherapy followed by reduced-dose RT [27,28], postoperative RT with either reduced dose or RT volume [29][30][31], and TORS followed by the deintensified adjuvant therapy [32].…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia is a major quality of life issue for patients treated for head and neck cancer treated either surgically or nonsurgically [19,20]. This potential longterm radiation damage has a profound impact on social functioning and mental health [21]. In order to reduce or limit these sequelae while maintaining excellent oncological outcomes, multiple paradigms have been explored with regard to treatment deescalation including cetuximab-RT [22,23], reduced-dose RT/CRT [24][25][26], induction chemotherapy followed by reduced-dose RT [27,28], postoperative RT with either reduced dose or RT volume [29][30][31], and TORS followed by the deintensified adjuvant therapy [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Patterson et al . showed that loneliness was linked to the depressive state in HNC survivors ( 20 ). They showed that quality of life improved when self-esteem and social relationships improved.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions of good and harm are much broader than will a person aspirate oral contents, and yet, this is so much the focus of risk feeding guidance and policies [5 ▪ ]. Advocating for restrictive consistencies or even nonoral feeding brings with it the very real harms of malnutrition and dehydration, withdrawal from society and isolation [23 ▪ ,24], family burden when trying to provide altered meals [25] and loss of patient and carer identity [26]. Comparing these harms with the less well evidenced potential benefits makes us question the received wisdom of traditional EDS intervention.…”
Section: Closer Inspection Of Principlesmentioning
confidence: 99%